Robotics in otolaryngology and head and neck surgery: Recommendations for training and credentialing: A report of the 2015 AHNS education committee, AAO‐HNS robotic task force and AAO‐HNS sleep disorders committee. (7th March 2016) - Gross, Neil D.; Holsinger, F. Christopher; Magnuson, J. Scott; Duvvuri, Umamaheswar; Genden, Eric M.; Ghanem, Tamer AH.; Yaremchuk, Kathleen L.; Goldenberg, David; Miller, Matthew C.; Moore, Eric J.; Morris, Luc GT.; Netterville, James; et al.
Abstract: Training and credentialing for robotic surgery in otolaryngology ‐ head and neck surgery is currently not standardized, but rather relies heavily on industry guidance. This manuscript represents a comprehensive review of this increasingly important topic and outlines clear recommendations to better standardize the practice. The recommendations provided can be used as a reference by individuals and institutions alike, and are expected to evolve over time. © 2016 Wiley Periodicals, Inc. Head Neck 38: E151–E158,